A Review of the Importance of Criticism Through Different Approaches - Qurratul Ain Sardar; Shabana M. Anwar; Anam Aqil khan (Journal of Management Practices, Humanities and Social Sciences, 2021)
This paper aims to discuss thoroughly different approaches to criticism with the help of pre-romantic aesthetics and their theories. The study, first, alludes to the 18th century pre-romantic aesthetics. Furthermore, the philosophical impact of Locke has been assessed in the light of the imagination theories. The theories of imagination given by Bruke and Addison have a lot of connection to aesthetics, which constitute part of imagination. Through a peculiar process, pleasure moves to be part of perception. Finding affirms that Locke’s philosophy relates to human compliance by means of which pre-romantic uses essential contextual treatises. The study adopts an analytical inquiry to accumulate data and then constructs a critical evaluation of factuality and erudition on the information. The findings of this research affirm that the emergence of knowledge has been debated for many centuries. Several literary epochs with a distinguished school of thought discuss and form inquiries. If rationalists portray human thoughts associated with the soul and cognitive views that a soul possesses from its inception, comparatively, Empiricists seem to have an approach that erupts from the perception and experiences as perception embarks on a journey to the blank paper of mind. If the reflection is there, it activates creating ideas, then this empiricism is directed to internality. Critics (Bruke & Addison) may be considered empiricists critics of the pre-romantic era.